Pembinaan Generasi Muda dalam Pengembangan Ekonomi Kreatif di Kota Langsa - Halida Bahri; Sambo, Masriadi (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2023)
The current development of information and communication technology has encouraged the younger generation to become economically independent by developing a creative. Service activities carried out aim to educate in the form of training for content creators at Langsa City. This service targets a group of youth known as generation Z or the millennial generation. They are now the creators of various new media platforms with the concept of profit sharing and endorsers. However, it has not been able to increase revenue. So that it is known, the competence to produce videos, edit, to market videos to social media channels is not owned comprehensively. From a technological point of view, they also have not mastered coding techniques by maximizing social media tools and search engine optimization (SEO). The results of this activity show that all participants who took part in this activity have increased their knowledge and understanding of how to produce and market content through all social media in the world